Improvement and evaluation of debris coolability analysis module in severe accident analysis code SAMPSON using LIVE experiment. (February 2017) - Wei, Hongyang; Erkan, Nejdet; Okamoto, Koji; Gaus-Liu, Xiaoyang; Miassoedov, Alexei
Highlights: Debris coolability analysis module in SAMPSON is validated. Model for heat transfer between melt pool and pressure vessel wall is modified. Modified debris coolability analysis module is found to give reasonable results. Abstract: The purpose of this work is to validate the debris coolability analysis (DCA) module in the severe accident analysis code SAMPSON by simulating the first steady stage of the LIVE-L4 test. The DCA module is used for debris cooling in the lower plenum and for predicting the safety margin of present reactor vessels during a severe accident. In the DCA module, the spreading and cooling of molten debris, gap cooling, heating of a three-dimensional reactor vessel, and natural convection heat transfer are all considered. The LIVE experiment is designed to investigate the formation and stability of melt pools in a reactor pressure vessel (RPV). By comparing the simulation results and experimental data in terms of the average melt pool temperature and the heat flux along the vessel wall, a bug is found in the code and the model for the heat transfer between the melt pool and RPV wall is modified. Based on the Asfia–Dhir and Jahn–Reineke correlations, the modified version of the DCA module is found to give reasonable results for the average melt pool temperature, crust thickness in the steady state, and crust growth rate.